Cooling of liquid in a tube under rotation - Wong, Kian Lin. (2011)
Polymerase chain reaction (PCR) is a prevalent scientific technique in molecular biology used to amplify a single, or a few copies of, a piece of DNA across several orders of magnitude, generating thousands to millions of copies of a particular DNA sequence. This report examines the current method of polymerase chain reaction that utilizes Coriolis and Centrifugal effects produced by rotation of PCR cone tubes. During the rotation, the internal circulatory rates, mixing speed increase and temperature homogenization is attained rapidly. Computational Fluid Dynamics analysis were carried out to investigate the complex three-dimensional internal fluid motion of the reaction mixture generated through the rotation of PCR tubes mounted in a disk-formed rotor. The computational flow modelling evaluation of the rotational effects on the fluid motion are developed by using Navier-Stokes equations based on the standard laminar model. By using computational fluid dynamics (CFD), the time development of the flow can be investigated in detail. Due to the rotation, an intricate azimuthal boundary layer flow is presented and explained. Last but not least, this report discusses a possible additional improvement motion modification that will be able to enhance the temperature homogenization.